Kajian Sosial Ekonomi Kerajinan Gerabah Plancungan Ponorogo, 2012-2022 - Sriweni, Erwina Yulia; Huda, Khoirul; Wibowo, Anjar Mukti (Universitas Hamzanwadi, 2023)
The problems faced by pottery craftsmen in the village of Plancungan Slahung, Ponorogo Regency, internally include limited capital, the raw material (clay) used to make handicrafts is quite limited so that the craftsmen have to buy from other villages, and the equipment used is very simple. The aim of the research is to examine the socio-economic development of pottery in Plancungan Ponorogo in the 2012-2022 period. This type of research uses a qualitative descriptive approach. The location of this research was conducted in Plancungan Village, Slahung District, Ponorogo Regency, East Java Province. The source of the data used in this research is pottery in the village of Plancungan. The application of the method is designed through heuristics using interviews, observations and document analysis. Then criticize the source with internal and external concepts. Then proceed with interpreting through a socio-economic study approach and written in narrative with a scientific manuscript model. The results of the study show that from 2012 to 2022 the traditional Plancungan pottery craft will continue to change as time goes by, starting with the variety and tools used. This also affects the social and economic life of the artisans, because this work is a source of livelihood for most people. So that the social and economic life of the community depends on the existence of the pottery produced, which of course is made as good as possible even though it is still traditional, so that it can be competitive with products and the times.Permasalahan yang dihadapi para pengrajin gerabah di Desa Plancungan Slahung Kabupaten Ponorogo dalam lingkup internal diantaranya yaitu terbatasnya permodalan yang dimiliki, bahan mentah (tanah liat) yang digunakan untuk membuat kerajinan cukup terbatas sehingga para pengrajin harus membeli ke desa lain, dan peralatan yang digunakan sangat sederhana. Tujuan penelitian untuk mengkaji perkembangan sosial ekonomi gerabah di Plancungan Ponorogo rentang 2012-2022. Jenis penelitian ini menggunakan pendekatan metode sejarah. Lokasi penelitian ini dilakukan di Desa Plancungan Kecamatan Slahung Kabupaten Ponorogo Provinsi Jawa Timur. Penerapan metode dirancang melalui heuristik dengan menggunakan wawancara, pengamatan dan analisis dokumen. Kemudian mengkritisi sumber dengan konsep internal dan eksternal. Lalu dilanjutkan dengan menginterpretasi melalui pendekatan kajian sosial ekonomi dan ditulis secara narasi dengan model manuskrip ilmiah. Hasil penelitian menunjukkan bahwa tahun 2012 sampai 2022 kerajinan gerabah tradisional Plancungan terus berubah seiring berkembangnya zaman mulai ragam dan alat yang dipakainya. Hal tersebut juga berpengaruh terhadap kehidupan sosial dan ekonomi perajinnya, oleh karena pekerjaan ini merupakan salah satu yang dijadikan sumber pencaharian sebagian besar masyarakat. Sehingga kehidupan sosial dan ekonomi masyarakat bergantung dengan eksistensi gerabah yang dihasilkan yang sudah barang tentu diupayakan dibuat sebaik mungkin meskipun masih tradisional, supaya mampu berdaya saing terhadap produk dan perkembangan zaman.